Genetic characterization and clinical implications of human papillomavirus type 16 (HPV16) variants from northeastern Argentina. - Badano, Ines (2015)
BACKGROUND: Human papillomavirus type 16 (HPV16) plays a central role in the development of cervical cancer. Worldwide studies indicate the existence of HPV16 variants that show different geographic distributions and oncogenic potential. OBJECTIVE: Our goal was to describe the genetic variation of HPV16 isolates identified in urban women with different grades of cervical lesions living in northeastern Argentina. STUDY DESIGN: We analyzed 116 HPV16-positive cervical samples (16 NLIM, 62 L-SIL, 16 H-SIL and 22 cervical cancer) from patients attending health centers in Misiones (Argentina) during 2006-13. HPV16 isolates were genetically characterized through PCR amplification and direct sequencing of 364 bp within the long control region, and the resulting sequences classified into variants based on phylogenetic analysis (lineages A, B, C and D). A potential association between HPV16 variants and lesion grade was evaluated through an odds ratio (OR) test. A temporal framework for the origin of HPV16 variants was assessed through coalescence analysis (BEAST v 1.7.5). RESULTS: Phylogenetic analysis of HPV16 sequences showed that 92.1% of the samples clustered with lineage A, and 6.9% to lineage D. HPV16 variants from lineage D were more frequently associated with high-grade lesions and cancer (HSIL+) than lineage A variants at an OR of 13.8 (1.6-117.0). The time to most common recent ancestor (tMCRA) of all variants was 119,103 years before present (HPD 95%=48,486-197,239), a date consistent with the time frame for modern human evolution. CONCLUSION: Our results suggest that HPV16 variants from lineage D may represent an additional risk factor for the development of cervical cancer in women living in northeastern Argentina. This study provides new information about viral isolates present in Argentina that will contribute to the monitoring of HPV16 infection in the vaccine era.